Rhizobacteria from Brazilian semiarid biome as growth promoters of soybean (Glycine max L.) under low water availability - Braga, Ana Paula Andrade (2022)
Caatinga is the predominant biome in the Brazilian semiarid region. Its vegetation is composed by plants and microorganisms with high tolerance to drought. Microorganisms associated with plants in this biome can develop mechanisms to protect cells from water stress and desiccation. The aim of this study was to identify plant growth-promoting rhizobacteria associated with the drought-tolerant legume Mimosa artemisiana and to examine their effect on the growth of soybean (Glycine max L.) under drought condition (irrigation with 30% of field capacity). Rhizospheric soil was collected along the Caatinga (In the States of Bahia and Pernambuco) at 4 collection points, totaling sixty subsamples. Xerotolerant bacteria with plant growth-promotion characteristics were isolated in a selective culture medium for diazotrophic bacteria. Two strains of the genera Bacillus and one Paenibacillus were promising in in vitro and in vivo tests. Both were able to grow in a medium with low water availability (0.919 Aw) and could produce exopolysaccharides and indole acetic acid (up to 130 µg mL−1). In addition, they produced 1-aminocyclopropane-1-carboxylate (ACC) deaminase and formed biofilms under drought conditions. The inoculation with the isolated strains in the seedling root system mitigated the adverse effects of drought, increasing roots and shoots dry weights of soybean seedlings compared with non-inoculated.